Pengembangan Media Video Animasi Kartun Pada Tema 2 Subtema 1 Kelas V Sekolah Dasar - Sella Pebriani; Dea Mustika (Journal on Education, 2023)
This research is motivated by problems in thematic learning theme 2, sub-theme 1 learning 1 and 2. The teacher does not yet have the right learning media for this thematic learning. This research is an ADDIE model development research with 5 stages consisting of (1) Analysis, (2) Design (Design), (3) Development (Development), (4) Implementation (Implementation), (5) Evaluation (Evaluation). Which aims to produce learning media in the form of animated cartoon videos in thematic learning. The results of this study are in the form of cartoon animation video media in thematic learning specifically on theme 2 sub-themes 1 class V Elementary School learning 1 and 2. In the first lesson there are Indonesian and Natural Sciences subjects regarding respiratory organs and systems in animals, while in the second lesson there are science, Indonesian, and SBdP subjects regarding respiratory organs and systems in humans. Validation results are also collected based on validation by material experts, design experts, and linguists. In the material expert aspect, 90.30% is in the very valid category, the design expert aspect is 80.29% in the quite valid category, and the linguist aspect is 98.17% in the very valid category. Overall the validity of cartoon animation video media in learning theme 2 sub-themes 1 class V of Elementary School obtained an average of 93% with a very valid category. Learning media developed through animated cartoon videos are very effective for students in thematic learning in elementary schools